Lateral release of proteins from the TOM complex into the outer membrane of mitochondria - Harner, Max; Neupert, Walter; Deponte, Marcel (The EMBO journal, 2011)
The TOM complex mediates import of mitochondrial proteins. Here, this complex is also shown to promote lateral release of proteins into the outer membrane
Gesehen am 03.08.2022